Second - order approximation of intraparticle mass transfer rate in adsorption processes - Georgiou, Andreas; Kupiec, Krzysztof; Christodoulides, Paul (My University, 2004)
A second-order approximation of adsorbate uptake rate is presented. The derivation of this approximation is based on the methodology developed by Georgiou & Kupiec (1996). Computations have been performed for different pellet geometries and boundary conditions for which analytical solutions are available. The results obtained are of high accuracy, significantly improving on other available approximations. An illustration of the application of the new model for kinetic parameters estimation is presented.